'I shared the joy': sport-related social support and communality on Instagram. Issue 2 (26th May 2020) - Ehrlén, Veera; Villi, Mikko
Abstract : The popularity of sharing photographs on digital platforms has increased significantly due to the communicative affordances of mobile media and the emergence of photo-sharing applications, such as Instagram. In this paper, we examine how social support and communality can be built and reinforced through digital visual communication. We focus especially on photo sharing in the context of recreational climbing and trail running. In a qualitative study with Finnish climbers and runners, we asked what meanings sports practitioners ascribe to the practice of sharing and observed how they communicate these meanings through photographs. The results indicate that different types of visual content build and reinforce communality in distinct ways. Whereas inspirational photographs drive practitioners to explore, motivational photographs pull practitioners to keep going through goal setting and peer support. We conclude that visual communication on Instagram mediates a stream of momentary encounters between practitioners that merge into communally meaningful experiences. Thus, we assert that in the context of recreational sport subcultures, photo sharing not only facilitates social relationships but can be perceived as a meaningful social practice that is integral to reinforcing physical activity.